(untitled) (Altre Modernità, 2019)
Websites are popular platforms for institutional Tourist Boards that want to promote their territories to visitors from all over the world. When tourism promotion is directly conducted by local institutions it entails greater responsibilities for the promoters since they are the real, actual territory introducing itself to prospective tourists. Therefore, the construction of the territorial image is fundamental to convey the aspects that best symbolize the land and that, eventually, will be the reason why tourists will choose to visit the area. This study investigates how local institutions in the Italian region of Veneto promote their districts (a.k.a. ‘provinces’) both in English and in Italian. To do so, the official tourism websites of the seven Veneto provinces are considered. The corpora, composed of texts taken from the websites, are examined quantitatively and qualitatively to identify the most recurrent keywords used in the texts. The aim is to identify the most representative aspects chosen by the seven territories as their symbolic markers, i.e. elements typical of a destination that are selected to provide an iconic, but also stereotypical, image of the local culture they are promoting.